Association between risk disclosure and (in) existence of corporate reputation of publicly traded companies in Brazil - Santos, Beatriz Alves dos; Maia, Anna Beatriz Grangeiro Ribeiro; Vasconcelos, Alessandra Carvalho de (Revista de Administração da UFSM, 2022)
Purpose - To analyze the possible association between non-financial risk disclosure and the (in) existence of reputation in the most prominent Brazilian publicly traded companies considering the legitimacy theory. Design/methodology/approach - The sample assembles 118 corporations listed on B3 and 345 reference forms from 2006 to 2018. In the analysis of corporate reputation, the presence or absence on ISE and, or ICO2 from B3 was considered. For non-financial risk disclosure, a factor checklist containing 31 risks was taken, categorized under operational, damage, integrity, and strategic risks, from the analysis of Reference Forms. A tree regression, a multiple correspondence analysis, and a T-test of the difference between means were used for data analysis. Findings - There is scientific evidence that the companies with reputations demonstrate non-financial risk disclosure superior to the others. This behavior is confirmed in the subcategories of integrity and strategic risks. Moreover, risk factors in the subcategory of integrity risks were crucial to non-financial risk disclosure. Originality/value - This research paves the way to deepen the early debate surrounding risk disclosure and corporate reputation, especially regarding the quality of non-financial risk disclosure.